Compositional dependence of structures and hydrogen evolution reaction activity of platinum-group-metal quinary RuRhPdIrPt alloy nanoparticles. Issue 44 (12th May 2022) - Maruta, Yuto; Kusada, Kohei; Wu, Dongshuang; Yamamoto, Tomokazu; Toriyama, Takaaki; Matsumura, Syo; Seo, Okkyun; Yasuno, Satoshi; Kawaguchi, Shogo; Sakata, Osami; Kubota, Yoshiki; Kitagawa, Hiroshi
Abstract : Platinum-group-metal quinary RuRhPdIrPt alloy nanoparticles were synthesised with compositions slightly away from equimolar, and their crystal, electronic structures and catalytic activity for hydrogen evolution reaction were investigated. Abstract : Platinum-group-metal quinary RuRhPdIrPt alloy nanoparticles were synthesised with compositions slightly away from equimolar, and their crystal and electronic structures were investigated. Their lattice constant changed linearly with composition, while the d-band centre changed nonlinearly. Their catalytic activities for the hydrogen evolution reaction were not correlated with their d-band centre.